2016
DOI: 10.3892/etm.2016.3313
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c modulates the mitochondrial signaling pathway and polymorphonuclear neutrophil apoptosis in bile duct-ligated rats

Abstract: Abstract. It has been observed that polymorphonuclear neutrophils (PMN) increase in number and function during obstructive jaundice (OJ). However, the precise mechanisms underlying PMN apoptosis during OJ remain poorly understood. The aim of the present study was to investigate the modulation of cytochrome c (Cytc) on the mitochondrial signaling pathway in bile duct-ligated (BDL) rats and the effect on PMN apoptosis following the intravenous administration of Cytc. Rats were randomly divided into four groups: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
1
12
0
2
Order By: Relevance
“…The existence and function of the neutrophils in OJ are the focus of many studies, which have demonstrated overproduction of neutrophils in human bone marrow and inhibition of PMN apoptosis in mice, leading to increased neutrophils counts 12,13 . However, little was known about the fate of the neutrophils in OJ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence and function of the neutrophils in OJ are the focus of many studies, which have demonstrated overproduction of neutrophils in human bone marrow and inhibition of PMN apoptosis in mice, leading to increased neutrophils counts 12,13 . However, little was known about the fate of the neutrophils in OJ.…”
Section: Discussionmentioning
confidence: 99%
“…OJ patients had increased neutrophil counts 12 . Furthermore, neutrophil apoptosis was inhibited in bile duct‐ligated rats, 13 as well as aberrant phagocytic function 14 . Notably, these neutrophil dysfunctions were corrected after biliary drainage 10,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Подобное состояние двух оксидоредуктаз цикла Кребса характеризует субстратный поток высокой интенсивности, что положительно повлияет на активность аэроб-ного дыхания. Необходимо отметить, аэробное дыхание вносит незначительный вклад в общую энергетику нейтрофильных гранулоцитов, од-нако высокая активность дыхательной цепи мо-жет стимулировать вхождение клетки в апоптоз [12,21]. На 24 сутки послеоперационного периода у больных РГП в нейтрофилах крови наблюдает-ся значительное снижение активности НАДН-зависимой реакции МДГ.…”
Section: Discussionunclassified
“…Экспрессия рецепторов для Fc-фрагмента иммуноглобулинов на поверхности нейтрофилов формирует пул армированных фагоцитов, участвующих в процессе антитело-зависимой цитотоксичности [10,11,26]. Учи-тывая, что все регуляторные и антигенные мо-лекулы реализуют свое воздействие на клетку через рецепторы, влияя на экспрессию генов, модулируя энергетические и пластические реакции, функциональные проявления ней-трофилов не могут не иметь метаболической основы [3,12,23]. РГП сопровождается избы-точным поступлением в биологические среды организма микробных антигенов и бактери-альных токсинов, источниками которых явля-ются гнойно-деструктивные очаги в брюшной полости, перитонеальный экссудат и парали-тически измененные петли кишечника [4,18].…”
Section: Introductionunclassified
“…It has been demonstrated that I/R-induced oxidative stress is a pivotal factor which leads to mitochondrial dysfunction [ 7 ]. I/R induced the upregulation of proapoptotic protein Bax and downregulation of antiapoptotic protein BCL2 which will lead to mitochondrial membrane permeability changes (the mitochondrial permeability transition pore (MPTP) opening, which in turn triggers apoptosis) and the loss of transmembrane potential [ 8 ]; then, cytochrome c and other proteins will be released from the mitochondria into the cytoplasm, which was considered to be a critical step in the mitochondrial apoptotic pathway [ 9 ]; finally, cytochrome c released into the cytoplasm induced caspase activation and cell apoptosis [ 10 ]. Therefore, maintaining EC and mitochondrial functional stability is a corking therapeutic strategy for mitigation of I/R injury.…”
Section: Introductionmentioning
confidence: 99%